KURIKULUM MERDEKA: PERSEPSI GURU TENTANG IMPLEMENTASI DALAM PENGAJARAN BAHASA INGGRIS DI SMKN 1 POLEWALI - Masyithah NR, Nurul; Muhayyang, Maemuna; Aeni, Nur; Dzhelilov, Akhtem A (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aimed to shed light on how is the teachers'' perception on the implementation of Merdeka Curriculum in Teaching English at SMKN 1 Polewali, this research is a qualitative research approach with a phenomenology descriptive design. The researcher using observation, interview and documentation to collect the data. Based on the observation and interview that have been done, the researcher found that the teachers'' perceptions reveal broad and narrow views. While appreciating curriculum flexibility for tailored learning and recognizing positive outcomes like increased student creativity and participation, some express concerns about limitations and administrative burdens. The teachers'' reveal their perception about how the merdeka curriculum giving teachers flexibility in teaching, enhancing student’s creativity, utilizing student-centred teaching method, seamless technology integration and emphasize the importance of reflection process in learning, In conclusion, the Merdeka Curriculum positively impacts the learning environment at SMK 1 Polewali, fostering dynamism and responsiveness to student needs. Ongoing efforts to understand and address varied teacher perceptions are crucial for optimizing curriculum benefits and ensuring equitable outcomes for all stakeholders in the learning process. the findings of this study provide a foundation for the development of targeted teacher professional development programmes. These programmes can address key challenges identified in the study, such as adapting to curriculum updates, integrating technology and managing administrative burdens. When teachers are equipped with the necessary skills and support, they can face these challenges more effectively, which will ultimately improve the implementation of Merdeka Curriculum